Heterogeneous solid catalyst and method for preparing styrylphenol polyoxyethylene ether by using heterogeneous solid catalyst
By using heterogeneous solid catalysts, composed of porous polymer microspheres and perfluorosulfonic acid polymers, the problems of low styrene phenol polyether content and high foam stability in the prior art are solved, and efficient preparation is achieved Styrene phenol polyoxyethylene ether improves the purity and defoaming properties of the product, and the catalyst can be reused and meets environmental protection requirements.
Patent Information
- Application Number
- CN202411635869.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-15
- Publication Date
- 2025-02-14
AI Technical Summary
In the prior art, when preparing styrene phenol polyoxyethylene ether, the styrene phenol polyether content is low, the foam stability is high, it is difficult to defoam, and the catalyst residue is difficult to remove, which affects the effect of the developer.
Using heterogeneous solid catalyst, consisting of porous polymer microspheres and perfluorosulfonic acid polymer supported on porous polymer microspheres, nano-inorganic solid material is used as a pore-making hard template, and combined with perfluorosulfonic acid polymer. Swelling and dispersing to prepare a catalyst with high catalytic properties and reusable.
The content of styrene phenol polyether is improved, foam stability is reduced, defoaming performance is enhanced, catalyst residue is reduced, product purity and application effect is improved, and the catalyst can be reused and meets environmental protection requirements.
Smart Images

Figure SMS_1 
Figure SMS_2
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of polyether preparation, and particularly relates to a heterogeneous solid catalyst and a method for preparing styrylphenol polyoxyethylene ether by using the same. Background Art
[0002] Styrylphenol polyoxyethylene ether surfactant is an important component of the developer formula in advanced photolithography process, and its performance directly affects the development effect of advanced process. The main components of styrylphenol polyoxyethylene ether surfactant are distyrylphenol polyoxyethylene ether, as well as a small amount of monostyrylphenol polyoxyethylene ether and tristyrylphenol polyoxyethylene ether. At present, the wetting performance of styrylphenol polyoxyethylene ether has reached a high level, but the content of distyrylphenol polyoxyethylene ether is still low, the foam is large, and it needs to be further improved. In terms of defoaming performance, the main influencing factor is the residual phenol polyether. Phenol polyether is the main impurity of styrylphenol polyoxyethylene ether, and its source is the ethoxylation reaction of unreacted free phenol in diphenylethylphenol and ethylene oxide. From the defoaming mechanism of surfactants, it can be seen that small molecular phenol polyethers are interspersed between styrylphenol polyoxyethylene ethers, which increases the surface strength of the liquid film, thereby increasing the stability of the foam, which is not conducive to defoaming. In terms of purity, it is mainly impurities such as acid and metal ions. Acid catalysts are homogeneous catalysts for the synthesis of distyrylphenol. Although they are highly active, the catalysts remain in the product and are difficult to remove. They also form salts with alkaline substances in the developer formula, directly affecting the developer effect. Metal ions mainly come from ethoxylated alkaline metal catalysts, which easily form salts with the acid catalysts in the previous step. They are highly soluble in the product and difficult to remove, resulting in a large amount of solid waste, which is not in line with the development trend of clean and environmental protection.
[0003] The preparation of styrylphenol polyoxyethylene ether is divided into two parts, first styrylphenol (mainly distyrylphenol) is prepared by phenol and styrene alkylation, then styrylphenol polyether (mainly distyrylphenol polyether) is obtained by carrying out ethoxylation with ethylene oxide. In the early days, the catalyst used in alkylation reaction is the concentrated sulfuric acid. Adopting the concentrated sulfuric acid as catalyst has the advantage that it can react at a lower temperature, and the speed of response is faster, but the concentrated sulfuric acid has an oxidizing effect on the product, and is highly corrosive to the equipment, and the post-processing such as neutralization, filtration, and washing will be carried out in the production technique, and the process is loaded down with trivial details, the yield is low, and the product quality is limited. Also some people use other mineral acids such as hydrochloric acid, phosphoric acid or pyrophosphoric acid to replace the concentrated sulfuric acid, in order to reduce the severity of equipment corrosion and reaction, but because these catalysts all have strong acidity, the improvement degree to the problems occurring in the reaction is limited, and the products obtained therefrom color and luster is darker, which limits the product application. In order to overcome this shortcoming, some people try to adopt some heterogeneous catalysts to replace homogeneous catalysts gradually. Although these heterogeneous catalysts can solve the problem of equipment corrosion to a certain extent, there are still problems such as complex catalyst recovery and product post-processing, inability to reuse, and low content of distyrylphenol polyether in the prepared styrylphenol polyoxyethylene ether, which makes it impossible to achieve large-scale application in actual production.
[0004] Therefore, there is an urgent need to provide a heterogeneous solid catalyst that can be reused and can prepare distyrylphenol polyoxyethylene ether with a high content of distyrylphenol polyether and low foaming performance. Summary of the invention
[0005] The present invention aims to solve at least one of the technical problems existing in the above-mentioned prior art. To this end, the present invention provides a heterogeneous solid catalyst and a method for preparing styrylphenol polyoxyethylene ether using the same. The heterogeneous solid catalyst provided by the present invention has a stable structure and strong reusability, and can prepare styrylphenol polyoxyethylene ether with a high content of distyrylphenol polyether and low foaming performance.
[0006] The invention provides a method for preparing a heterogeneous solid catalyst.
[0007] Specifically, a method for preparing a heterogeneous solid catalyst comprises the following steps:
[0008] (1) mixing a nano inorganic solid material with a vinyl monomer, an olefinic phenyl monomer, an initiator, a porogen, and a solvent to obtain an oil phase; mixing water with a fatty acid ester sulfonate to obtain an aqueous phase; mixing the aqueous phase with the oil phase in a mass ratio of (1-5):1, heating, and performing a polymerization reaction to obtain polymer microspheres;
[0009] (2) mixing the perfluorosulfonic acid polymer with an ethanol solution to obtain a swelling dispersion;
[0010] (3) mixing the polymer microspheres prepared in step (1) with a hydrochloric acid solution, stirring for reaction, and obtaining porous polymer microspheres; directly adding the swelling dispersion prepared in step (2) after the reaction, heating and impregnating; then separating to obtain the impregnated porous polymer microspheres, and finally drying to obtain a heterogeneous solid catalyst;
[0011] The nano inorganic solid materials in step (3) are nano CaCO3 and nano Al2O3; the particle size of the nano CaCO3 is 150-300 nm, and the particle size of the nano Al2O3 is 30-90 nm; the mass ratio of the nano CaCO3 to the nano Al2O3 is (0.3-1.5):1;
[0012] The mass percentage of the hydrochloric acid solution in step (3) is 3%-6%;
[0013] The mass percentage of the ethanol solution in step (2) is 30%-70%.
[0014] In some embodiments of the present invention, the mass ratio of nano-CaCO3 to nano-Al2O3 in step (1) is (0.5-1):1.
[0015] In some embodiments of the present invention, the particle size of the nano-CaCO3 is 180-250nm, and the particle size of the nano-Al2O3 is 30-80nm.
[0016] In some embodiments of the present invention, the oil phase in step (1) comprises, by weight, 10-20 parts of nano-inorganic solid materials, 30-50 parts of vinyl monomers, 5-12 parts of olefinic phenyl monomers, 0.5-3 parts of initiators, 5-10 parts of porogens, and 10-50 parts of solvents; preferably, the oil phase comprises, by weight, 12-18 parts of nano-inorganic solid materials, 30-45 parts of vinyl monomers, 5-10 parts of olefinic phenyl monomers, 0.5-3 parts of initiators, 5-10 parts of porogens, and 20-40 parts of solvents.
[0017] In some embodiments of the present invention, the vinyl monomer is selected from at least one of methyl methacrylate, vinyl acetate, and methyl acrylate; the phenylene monomer is selected from at least one of dipropylenebenzene, divinylphenylmethane, and divinylbenzene; the initiator is selected from azobisisobutyronitrile and / or diisopropylbenzene peroxide; the solvent is selected from at least one of butanone or ethyl acetate; and the porogen is at least one of butanol or n-heptane.
[0018] In some embodiments of the present invention, in the aqueous phase, the mass ratio of water to fatty acid ester sulfonate is 10:(0.05-0.5). Preferably, the mass ratio of water to fatty acid ester sulfonate is 10:(0.1-0.5). The use of fatty acid ester sulfonate as a dispersant is conducive to more uniform dispersion of nano inorganic solid materials in the preparation of polymer microspheres through reasonable proportioning, thereby forming porous polymer microspheres with uniform pores.
[0019] In some embodiments of the present invention, the fatty acid ester sulfonate includes at least one of fatty acid methyl ester sulfonate, fatty acid ethyl ester sulfonate or fatty acid propyl ester sulfonate.
[0020] In some embodiments of the present invention, the mass ratio of the oil phase to the water phase is 1:(1-3); preferably, the mass ratio of the oil phase to the water phase is 1:(1.5-2.5).
[0021] In some embodiments of the present invention, the polymerization reaction temperature in step (1) is 70-80° C., and the polymerization reaction time is 3-5 hours.
[0022] In some embodiments of the present invention, the mass ratio of the perfluorosulfonic acid polymer to the ethanol solution in step (2) is 1:(3-8). Preferably, the mass ratio of the perfluorosulfonic acid polymer to the ethanol solution in step (2) is 1:(5-8).
[0023] In some embodiments of the present invention, the mass percentage of the ethanol solution in step (2) is 40%-60%.
[0024] In some embodiments of the present invention, the mass ratio of the polymer microspheres to the hydrochloric acid solution in step (3) is 1:(1-3). Preferably, the mass ratio of the polymer microspheres to the hydrochloric acid solution in step (3) is 1:(1.5-2.5).
[0025] In some embodiments of the present invention, the stirring reaction temperature in step (3) is 45-65° C., and the stirring reaction time is 1-5 hours.
[0026] In some embodiments of the present invention, the mass of the swelling dispersion added in step (3) is 1-3 times that of the hydrochloric acid solution.
[0027] In some embodiments of the present invention, the temperature of the heating and immersion in step (3) is 40-60°C, and the time of the heating and immersion is 1-5 hours; preferably, the temperature of the heating and immersion in step (3) is 45-55°C, and the time of the heating and immersion is 2-5 hours.
[0028] The invention also provides a heterogeneous solid catalyst.
[0029] Specifically, a heterogeneous solid catalyst is prepared by the above preparation method, wherein the heterogeneous solid catalyst consists of porous polymer microspheres and a perfluorosulfonic acid polymer loaded on the porous polymer microspheres.
[0030] The invention also provides a method for preparing styrylphenol polyoxyethylene ether.
[0031] Specifically, a method for preparing styrylphenol polyoxyethylene ether comprises the following steps:
[0032] (1) Phenol alkylation reaction: Phenol and the above-mentioned heterogeneous solid catalyst are placed in nitrogen and heated to 80-100° C., styrene is added dropwise under stirring, and the reaction is carried out by keeping the temperature. After the reaction is completed, the heterogeneous solid catalyst is recovered by solid-liquid separation to obtain styrylphenol;
[0033] (2) Ethylene oxide addition polymerization: Styrylphenol is heated to 100-110°C in a nitrogen atmosphere, vacuum dehydrated, and then a polymerization catalyst is added. The temperature is raised to 80-120°C in a nitrogen atmosphere, and ethylene oxide is metered into the reaction mixture. The reaction is carried out at 80-120°C and 0.1-0.4 MPa to obtain styrylphenol polyoxyethylene ether.
[0034] In step (1), the molar ratio of styrene to phenol is (1.8-2.5):1; preferably, the molar ratio of styrene to phenol is (2.0-2.3):1; further preferably, the molar ratio of styrene to phenol is (2.05-2.1):1.
[0035] In some embodiments of the present invention, the amount of the heterogeneous solid catalyst added is 0.5%-2% of the mass of the phenol; preferably, the amount of the heterogeneous solid catalyst added is 0.8%-1.5% of the mass of the phenol.
[0036] In some embodiments of the present invention, the addition polymerization catalyst in step (2) includes any one of an organic phosphazene salt, boron trifluoride ether complex, potassium methoxide, sodium methoxide, KOH, and NaOH.
[0037] In some embodiments of the present invention, the preparation method further includes a post-treatment step. Specifically, the post-treatment process is: neutralizing the crude styrylphenol polyoxyethylene ether obtained after the reaction is completed, heating it to 60-70°C with deionized water, adding an adsorbent after stirring, vacuuming and dehydrating after sufficient adsorption, cooling, and filtering to obtain styrylphenol polyoxyethylene ether.
[0038] Compared with the prior art, the present invention has the following beneficial effects:
[0039] (1) The present invention provides a heterogeneous solid catalyst, which is composed of porous polymer microspheres and a perfluorosulfonic acid polymer loaded on the porous polymer microspheres. The heterogeneous solid catalyst provided by the present invention has strong acidity, large specific surface area, and excellent catalytic performance. In the alkylation reaction of preparing styrylphenol polyoxyethylene ether, it is conducive to the generation of distyrylphenol, reduces the residual free phenol, and makes the prepared styrylphenol polyoxyethylene ether high in purity, low in phenol polyoxyethylene ether content, less foam, and easy to defoam; in the heterogeneous solid catalyst, the perfluorosulfonic acid polymer is tightly combined with the polymer microspheres, the structure is stable, and it can be recycled by simple separation after the reaction is completed. And compared with traditional homogeneous acidic catalysts, the heterogeneous solid catalyst provided by the present invention has less corrosiveness to equipment and strong reusability, which is conducive to direct application in actual production.
[0040] (2) In the preparation of the heterogeneous solid catalyst, the present invention uses a nano inorganic solid material as a pore-making hard template, disperses it in a polymer resin, and then dissolves and removes the nano inorganic solid material in an acid solution to obtain porous polymer microspheres; then the perfluorosulfonic acid polymer is swollen and dispersed, and the porous polymer microspheres are impregnated to obtain a heterogeneous solid catalyst loaded with the perfluorosulfonic acid polymer. The present invention selects nano CaCO3 and nano Al2O3 as nano inorganic solid materials, and controls the dosage ratio and particle size of nano CaCO3 and nano Al2O3. When the acid solution dissolves, it will preferentially react with CaCO3 to form pores with larger pore size; while reacting with Al2O3 to form smaller pores. By controlling the dosage ratio and particle size of nano CaCO3 and nano Al2O3, as well as the concentration of hydrochloric acid, pores with dense pores, uniform distribution and stable structure can be generated in an orderly manner, thereby making the prepared porous polymer microspheres have a large specific surface area and a stable structure. At the same time, the present invention adopts ethanol solution to swell and disperse the perfluorosulfonic acid polymer, and acts together with the hydrochloric acid solution that dissolves and removes the unreacted nano inorganic solid material, which is beneficial to further dispersion of the perfluorosulfonic acid polymer. The fully dispersed perfluorosulfonic acid polymer dispersion is more likely to enter the interior of the porous polymer microspheres to form a stable adhesion layer; and the process does not need to remove the unreacted hydrochloric acid solution, which can simplify the process. DETAILED DESCRIPTION
[0041] In order to make the technical scheme of the present invention more clearly understood by those skilled in the art, the following embodiments are listed for illustration. It should be pointed out that the following embodiments do not limit the protection scope of the present invention.
[0042] Unless otherwise specified, the raw materials, reagents or devices used in the following examples can be obtained from conventional commercial sources or by existing known methods.
[0043] Example 1
[0044] A method for preparing a heterogeneous solid catalyst comprises the following steps:
[0045] (1) By weight, 7 parts of nano-CaCO3 (particle size of 180-220 nm) and 7 parts of nano-Al2O3 (particle size of about 50-80 nm) were mixed with 20 parts of methyl methacrylate, 20 parts of vinyl acetate, 4 parts of divinylphenylmethane, 4 parts of divinylbenzene, 2 parts of azobisisobutyronitrile, 6 parts of butanol, and 30 parts of ethyl acetate to prepare an oil phase; water and fatty acid ester sulfonate were mixed in a mass ratio of 10:0.2 to prepare an aqueous phase; the aqueous phase and the oil phase were mixed in a mass ratio of 2:1, the temperature was raised to 75° C., and a polymerization reaction was carried out at a stirring speed of 200 rpm. After reacting for 4 hours, polymer microspheres were prepared;
[0046] (2) crushing a perfluorosulfonic acid polymer (Nafion), mixing it with a 50% ethanol solution at a mass ratio of 1:4, and fully swelling and dispersing it to obtain a swelling dispersion;
[0047] (3) mixing the polymer microspheres prepared in step (1) with a 5% hydrochloric acid solution (mass ratio of 1:2), heating to 55° C., and stirring for reaction for 2.5 hours to obtain porous polymer microspheres; directly adding the swelling dispersion prepared in step (2) after the stirring reaction, controlling the mass of the swelling dispersion to be twice that of the hydrochloric acid solution, and then heating to 55° C. and immersing for 3 hours; finally separating the immersed porous polymer microspheres, removing the solvent, and drying and solidifying at 120° C. to obtain a heterogeneous solid catalyst.
[0048] Example 2
[0049] A method for preparing a heterogeneous solid catalyst comprises the following steps:
[0050] (1) By weight, 6 parts of nano-CaCO3 (particle size of 180-220 nm) and 10 parts of nano-Al2O3 (particle size of about 50-80 nm) were mixed with 18 parts of methyl methacrylate, 24 parts of vinyl acetate, 5 parts of divinylphenylmethane, 5 parts of divinylbenzene, 2.5 parts of azobisisobutyronitrile, 5 parts of butanol, and 24.5 parts of ethyl acetate to prepare an oil phase; water and fatty acid ester sulfonate were mixed at a mass ratio of 10:0.3 to prepare an aqueous phase; the aqueous phase and the oil phase were mixed at a mass ratio of 2.2:1, the temperature was raised to 75° C., and a polymerization reaction was carried out at a stirring speed of 200 rpm. After reacting for 4 hours, polymer microspheres were prepared;
[0051] (2) crushing a perfluorosulfonic acid polymer (Nafion), mixing it with a 60% ethanol solution at a mass ratio of 1:4, and fully swelling and dispersing it to obtain a swelling dispersion;
[0052] (3) mixing the polymer microspheres prepared in step (1) with a 3.5% hydrochloric acid solution (mass ratio of 1:2), heating to 55° C., and stirring for reaction for 4 hours to obtain porous polymer microspheres; directly adding the swelling dispersion prepared in step (2) after the stirring reaction, controlling the mass of the swelling dispersion to be twice that of the hydrochloric acid solution, and then heating to 55° C. and immersing for 3 hours; finally separating the immersed porous polymer microspheres, removing the solvent, and drying and solidifying at 120° C. to obtain a heterogeneous solid catalyst.
[0053] Example 3
[0054] A method for preparing a heterogeneous solid catalyst comprises the following steps:
[0055] (1) By weight, 6 parts of nano-CaCO3 (particle size of 180-220 nm) and 10 parts of nano-Al2O3 (particle size of about 50-80 nm) were mixed with 18 parts of methyl acrylate, 24 parts of vinyl acetate, 5 parts of dipropylene benzene, 5 parts of divinyl benzene, 2.5 parts of azobisisobutyronitrile, 5 parts of butanol, and 24.5 parts of ethyl acetate to prepare an oil phase; water and fatty acid ester sulfonate were mixed at a mass ratio of 10:0.3 to prepare an aqueous phase; the aqueous phase and the oil phase were mixed at a mass ratio of 2.2:1, the temperature was raised to 75° C., and a polymerization reaction was carried out at a stirring speed of 200 rpm. After reacting for 4 hours, polymer microspheres were prepared;
[0056] (2) crushing a perfluorosulfonic acid polymer (Nafion), mixing it with a 40% ethanol solution at a mass ratio of 1:4, and fully swelling and dispersing it to obtain a swelling dispersion;
[0057] (3) mixing the polymer microspheres prepared in step (1) with a 6% hydrochloric acid solution (mass ratio of 1:1.5), heating to 55° C., and stirring for reaction for 2.5 hours to obtain porous polymer microspheres; directly adding the swelling dispersion prepared in step (2) after the stirring reaction, controlling the mass of the swelling dispersion to be twice that of the hydrochloric acid solution, and then heating to 55° C. and immersing for 3 hours; finally separating the immersed porous polymer microspheres, removing the solvent, and drying and solidifying at 120° C. to obtain a heterogeneous solid catalyst.
[0058] Example 4
[0059] A method for preparing a heterogeneous solid catalyst comprises the following steps:
[0060] (1) By weight, 7 parts of nano-CaCO3 (particle size of 180-220 nm) and 7 parts of nano-Al2O3 (particle size of about 50-80 nm) were mixed with 20 parts of methyl methacrylate, 20 parts of vinyl acetate, 4 parts of divinylphenylmethane, 4 parts of divinylbenzene, 2 parts of azobisisobutyronitrile, 6 parts of butanol, and 30 parts of ethyl acetate to prepare an oil phase; water and fatty acid ester sulfonate were mixed in a mass ratio of 10:0.2 to prepare an aqueous phase; the aqueous phase and the oil phase were mixed in a mass ratio of 2:1, the temperature was raised to 75° C., and a polymerization reaction was carried out at a stirring speed of 200 rpm. After reacting for 4 hours, polymer microspheres were prepared;
[0061] (2) crushing a perfluorosulfonic acid polymer (Nafion), mixing it with a 30% ethanol solution at a mass ratio of 1:4, and fully swelling and dispersing it to obtain a swelling dispersion;
[0062] (3) mixing the polymer microspheres prepared in step (1) with a 3% hydrochloric acid solution (mass ratio of 1:2), heating to 55° C., and stirring for reaction for 2.5 hours to obtain porous polymer microspheres; directly adding the swelling dispersion prepared in step (2) after the stirring reaction, controlling the mass of the swelling dispersion to be twice that of the hydrochloric acid solution, and then heating to 55° C. and immersing for 3 hours; finally separating the immersed porous polymer microspheres, removing the solvent, and drying and solidifying at 120° C. to obtain a heterogeneous solid catalyst.
[0063] Comparative Example 1
[0064] This comparative example provides a method for preparing a heterogeneous solid catalyst. The difference between comparative example 1 and example 1 is that the nano inorganic solid material used in comparative example 1 is 14 parts of nano CaCO3 (particle size is 180-220nm), and the rest is the same as example 1.
[0065] Comparative Example 2
[0066] This comparative example provides a method for preparing a heterogeneous solid catalyst. The difference between Comparative Example 2 and Example 1 is that the nano inorganic solid materials used in Comparative Example 2 are 2 parts of nano CaCO3 (particle size is 180-220nm) and 12 parts of nano Al2O3 (particle size is about 50-80nm), and the rest are the same as Example 1.
[0067] Comparative Example 3
[0068] This comparative example provides a method for preparing a heterogeneous solid catalyst. The difference between comparative example 3 and example 1 is that in step (2), the 50% ethanol solution is replaced by anhydrous ethanol, and the rest is the same as example 1.
[0069] Comparative Example 4
[0070] This comparative example provides a method for preparing a heterogeneous solid catalyst. The difference between comparative example 4 and example 1 is that the mass percentage of the hydrochloric acid solution in step (3) is 10%, and the rest is the same as example 1.
[0071] Comparative Example 5
[0072] This comparative example provides a method for preparing a heterogeneous solid catalyst. The difference between comparative example 5 and example 1 is that the mass percentage of the hydrochloric acid solution in step (3) is 1.5%, and the rest is the same as example 1.
[0073] Comparative Example 6
[0074] This comparative example provides a method for preparing a heterogeneous solid catalyst. The difference between comparative example 6 and example 1 is that after the stirring reaction in step (3) is completed, the reactants are filtered to remove the filtrate (to remove the unreacted hydrochloric acid solution), and the separated porous polymer microspheres are washed with water three times and dried at 80° C. to obtain dry porous polymer microspheres; and then the swelling dispersion prepared in step (2) is added. The remaining steps are the same as in example 1.
[0075] Application Examples
[0076] The heterogeneous solid catalysts prepared in the above examples and comparative examples were used as alkylation catalysts in the preparation of styrylphenol polyoxyethylene ethers, as follows:
[0077] A method for preparing styrylphenol polyoxyethylene ether comprises the following steps:
[0078] (1) Alkylation reaction: 255 g of phenol and 2.04 g of the above-mentioned heterogeneous solid catalyst were weighed and added into a four-necked flask. The temperature was raised to 95° C. under nitrogen, and 580 g of styrene was added dropwise under rapid stirring. The addition was completed over 1.5 hours. The temperature was kept warm and the reaction was continued until the refractive index (25° C.) of the product reached 1.5985-1.6020. When the reaction was complete, the temperature was lowered to 50° C., the styrene was removed by degassing, and the heterogeneous solid catalyst was separated from the reaction system by filtration to obtain styrylphenol.
[0079] (2) Ethylene oxide addition polymerization: 314 g of styrylphenol and 1 g of potassium hydroxide were weighed and added into an autoclave, and the temperature was raised to 100°C under nitrogen. After vacuum dehydration for 1 hour, 686 g of ethylene oxide was added. After the addition was completed, the reaction mixture was aged (95°C) until the pressure remained substantially unchanged, and the temperature was lowered and the mixture was discharged to obtain a crude product of styrylphenol polyoxyethylene ether.
[0080] (3) Post-treatment of polyether: Weigh the crude product of styrylphenol polyoxyethylene ether, neutralize it with acid, treat it with water and adsorbent, dehydrate and filter it to obtain the polyether product.
[0081] Product effect testing
[0082] (1) Color measurement: The color of styrylphenol polyoxyethylene ether products was measured using a platinum-cobalt colorimeter (model SD9012A). The test was performed three times under the same conditions, and the average value was taken as the test result.
[0083] (2) Liquid chromatography analysis (HPLC)
[0084] Agilent 1200 liquid chromatograph was used to analyze the component contents of styrylphenol polyoxyethylene ether products. The analysis conditions were: chromatographic column XDB-C18-B2, column temperature 40°C, methanol / water as solvent, and flow rate 1.0 mL / min.
[0085] (3) Foaming performance determination: According to the national standard "GB / T 13173-2021", the Ross-Miles method is used to determine the foaming performance of styrylphenol polyoxyethylene ether products.
[0086] The test results are shown in Table 1-Table 2.
[0087] Table 1
[0088]
[0089]
[0090] Table 2
[0091] index Bubble height / cm Defoaming time(s) Example 1 3.5 4s Example 2 3.9 6s Example 3 3.6 5s Example 4 4.7 11s Comparative Example 1 7.6 21s Comparative Example 2 7.2 19s Comparative Example 3 8.1 24s Comparative Example 4 6.9 17s Comparative Example 5 7.9 22s Comparative Example 6 8.5 27s
[0092] Note: Since the foam disappears within 5 minutes, the time of foam disappearance is recorded.
[0093] As shown in Table 1 and Table 2, the heterogeneous solid catalyst provided by Examples 1-4 of the present invention is used to prepare polyoxyethylene styrylphenol. In the alkylation reaction, the residual phenol can be reduced and the monostyrylphenol polyoxyethylene ether in the product can be reduced by designing the catalyst and controlling the amount of phenol and styrene; the generation of tristyrylphenol polyoxyethylene ether can also be reduced, so that the content of distyrylphenol polyoxyethylene ether is as high as 84.7%. And the prepared product is light in color and easy to defoam, which can better meet practical applications. More importantly, the heterogeneous solid catalyst provided by the present invention is used to prepare polyoxyethylene styrylphenol. After the reaction is completed, the catalyst can be recovered by simple separation treatment, and the recovered catalyst can be reused, and experiments have found that its catalytic performance is not easily weakened.
[0094] And the styrylphenol polyoxyethylene ether prepared by the heterogeneous solid catalyst utilizing the comparative example preparation, its content of distyrylphenol polyoxyethylene ether is low, and product color is dark, is difficult for defoaming, and has a serious impact on the application of product.Specific analysis, in comparative example 1, nano inorganic solid material only uses the larger nano CaCO of particle diameter, when adopting hydrochloric acid solution to dissolve, speed of reaction is fast, the hole formed is large, and easily collapses, and then affects the internal pore structure of porous polymer microsphere, is unfavorable for the attachment of perfluorosulfonic acid polymer.Therefore, its catalytic performance is not as good as embodiment 1, and within the same catalytic time, free phenol residual amount is large, generates a large amount of phenol polyoxyethylene ether, and monostyrylphenol polyoxyethylene ether and tristyrylphenol polyoxyethylene ether also can improve. In the comparative document 2, the amount of nano inorganic solid material nano CaCO3 is too small. When the hydrochloric acid solution is used for dissolution, the nano Al2O3 with a small particle size reacts slowly with the hydrochloric acid solution, and the dense pores are difficult to be completely generated, thereby reducing the richness of the pores inside the polymer microspheres, and the amount of perfluorosulfonic acid polymer attached is also reduced, which ultimately affects the performance of the catalyst and increases the impurities of the prepared styrylphenol polyoxyethylene ether. In comparative example 3, only anhydrous ethanol is used to swell and disperse the perfluorosulfonic acid polymer. The anhydrous ethanol and the hydrochloric acid solution that has not reacted in step (3) cannot swell and disperse the perfluorosulfonic acid polymer well, and then the swelling dispersion cannot enter the porous polymer microspheres well to achieve attachment during immersion. In comparative example 4, 10% hydrochloric acid solution was used to treat the polymer microspheres. The hydrochloric acid solution with too high a concentration reacted violently with Al2O3 and CaCO3, which had an adverse effect on the pore structure inside the polymer microspheres, resulting in poor pore uniformity and unstable structure, which was not conducive to the attachment of the perfluorosulfonic acid polymer; and the catalyst had poor stability when reused. In comparative example 5, 1.5% hydrochloric acid solution was used to treat the polymer microspheres. The concentration of hydrochloric acid was too low, and the pores inside the polymer microspheres were not completely formed at the same time; and because the concentration of hydrochloric acid was too low, the residual acid solution after the reaction was reduced, which was not conducive to the further swelling and dispersion of the perfluorosulfonic acid polymer. Therefore, the amount of attachment of the prepared catalyst perfluorosulfonic acid polymer was small, and the catalytic performance decreased. In comparative example 6, the unreacted hydrochloric acid solution was removed in step (3), and the perfluorosulfonic acid polymer swollen with ethanol solution could not be further dispersed by the hydrochloric acid solution. During the impregnation, the swelling dispersion that was not well dispersed could not enter the interior of the porous polymer microspheres well, thereby reducing the catalyst performance.
[0095] The above-mentioned embodiments only express several implementation methods of the present invention, and the description thereof is relatively specific and detailed, but it cannot be understood as limiting the scope of the patent of the present invention. It should be pointed out that, for ordinary technicians in this field, several variations and improvements can be made without departing from the concept of the present invention, which all belong to the protection scope of the present invention. Therefore, the protection scope of the patent of the present invention shall be subject to the attached claims.
Claims
1. A method for preparing a heterogeneous solid catalyst, characterized in that: The following steps are involved: (1) mixing a nano inorganic solid material with a vinyl monomer, an olefinic phenyl monomer, an initiator, a porogen, and a solvent to obtain an oil phase; mixing water with a fatty acid ester sulfonate to obtain an aqueous phase; mixing the aqueous phase with the oil phase in a mass ratio of (1-5):1, heating, and performing a polymerization reaction to obtain polymer microspheres; (2) mixing the perfluorosulfonic acid polymer with an ethanol solution to obtain a swelling dispersion; (3) mixing the polymer microspheres prepared in step (1) with a hydrochloric acid solution, stirring for reaction, and obtaining porous polymer microspheres; directly adding the swelling dispersion prepared in step (2) after the reaction, heating and impregnating; then separating to obtain the impregnated porous polymer microspheres, and finally drying to obtain a heterogeneous solid catalyst; The nano inorganic solid materials in step (3) are nano CaCO3 and nano Al2O3; the particle size of the nano CaCO3 is 150-300 nm, and the particle size of the nano Al2O3 is 30-90 nm; the mass ratio of the nano CaCO3 to the nano Al2O3 is (0.3-1.5):1; The mass percentage of the hydrochloric acid solution in step (3) is 3%-6%; The mass percentage of the ethanol solution in step (2) is 30%-70%.
2. The preparation method according to claim 1, characterized in that: The mass ratio of nano-CaCO3 to nano-Al2O3 in step (1) is (0.5-1):
1.
3. The preparation method according to claim 1 or 2, characterized in that: In parts by weight, the oil phase in step (1) comprises 10-20 parts of nano inorganic solid material, 30-50 parts of vinyl monomer, 5-12 parts of olefinic phenyl monomer, 0.5-3 parts of initiator, 5-10 parts of porogen and 10-50 parts of solvent.
4. The preparation method according to claim 3, characterized in that: The vinyl monomer is selected from at least one of methyl methacrylate, vinyl acetate, and methyl acrylate; the olefinic phenyl monomer is selected from at least one of dipropylene benzene, divinylphenyl methane, and divinyl benzene; the initiator is selected from azobisisobutyronitrile and / or diisopropylbenzene peroxide; the solvent is selected from at least one of butanone or ethyl acetate; and the porogen is at least one of butanol or n-heptane.
5. The preparation method according to claim 1 or 2, characterized in that: In the water phase, the mass ratio of the water to the fatty acid ester sulfonate is 10:(0.05-0.5).
6. The preparation method according to claim 1 or 2, characterized in that: The mass ratio of the perfluorosulfonic acid polymer to the ethanol solution in step (2) is 1:(3-8).
7. The preparation method according to claim 1 or 2, characterized in that: The mass ratio of the polymer microspheres to the hydrochloric acid solution in step (3) is 1:(1-3).
8. The preparation method according to claim 7, characterized in that: The mass of the swelling dispersion added in step (3) is 1-3 times that of the hydrochloric acid solution.
9. A heterogeneous solid catalyst, characterized in that The heterogeneous solid catalyst is prepared by the preparation method described in any one of claims 1 to 8, and is composed of porous polymer microspheres and a perfluorosulfonic acid polymer supported on the porous polymer microspheres.
10. A method for preparing styrylphenol polyoxyethylene ether, characterized in that: The following steps are involved: (1) Phenol alkylation reaction: phenol and the heterogeneous solid catalyst according to claim 9 are placed in a nitrogen atmosphere and heated to 80-100° C., styrene is added dropwise under stirring, and the reaction is carried out by heat preservation. After the reaction is completed, the heterogeneous solid catalyst is recovered by solid-liquid separation to obtain styrylphenol; (2) Ethylene oxide addition polymerization: the styrylphenol is heated to 100-110°C in a nitrogen atmosphere, vacuum dehydrated, and then a polymerization catalyst is added. The temperature is raised to 80-120°C in a nitrogen atmosphere, and ethylene oxide is metered into the mixture. The mixture is reacted at 80-120°C and 0.1-0.4 MPa to obtain styrylphenol polyoxyethylene ether. In step (1), the molar ratio of the styrene to the phenol is (1.8-2.5):1.